Isolation, Characterization and Screening for Anticancer and Antimicrobial Properties of the Crude Extract from Genus Neosartorya - Supattra Poeaim; Kongluekai Tongkantom; Prapaiporn Jabamrung; On Bo-kaew; Mayamor Soytong (My University, 2016)
The genus Neosartorya, the sexual states of Aspergillus, belongs to the Eurotiales which have been reported for compounds with bioactivities such as antimicrobial, antimalarial and cytotoxicity.The objective of this research was to isolate, identify and screening for anticancer and antimicrobial properties of the ethyl acetate crude extract from Neosartorya.Neosartorya sp. was isolated from soil in Chiang Mai province, Thailand by the soil plate technique.The samples were identified base on morphology and DNA sequencing: Internal transcribed spacer (ITS), ß-tubulin and calmodulin as Neosartorya hiratsukae and Neosartorya pseudofischeri.For in vitro cytotoxicity activity by MTT assay using eight cell lines (MCF-7, P388, HeLa, Vero, L929, KB, HT-29 and HepG2).The crude ethyl acetate extract of N. hiratsukae and N. pseudofischeri showed the highest potency against the L929 cell line with the 50% inhibitory concentration (IC 50 ) value of 144.31 and 267.73 µg/ml, respectively.The antimicrobial properties of crude extract were evaluated using disc diffusion method against five bacteria strain: Bacillus subtilis, Staphylococcus aureus, Micrococcus luteus, Escherichia coli and Pseudomonas aeruginosa.The extract was well inhibited the growth of gram positive pathogenic bacteria: B. subtilis, S. aureus and M. luteus.The results indicate its possible potential with the production of other bioactive agents for future anticancer and antibiotic drug development.
Keywords: Isolation; Essential Oils and Antimicrobial Activity